Temporal microbial colonization on different forages is driven by the rumen environmental conditions - X. Xie; J. K. Wang; J. X. Liu; L. L. Guan; A. L. A. Neves (Animal Microbiome)
Abstract The rumen is one of the four compartments of the ruminant stomach and houses a diverse array of anaerobic microbes that play a crucial role in feed digestion and volatile fatty acid (VFA) production. The aim of this study was to explore how two different in vivo rumen environmental conditions, AHR (created from sheep-fed alfalfa hay) and CSR (created from sheep-fed corn stover), affect fiber digestion and rumen bacterial colonization in relation to two types of forage, alfalfa hay (AH) and corn stover (CS). Both AH and CS forages were subjected to in-sacco incubation in AHR and CSR conditions for a period of 48 h. The results revealed that CSR exhibited a less variant pH, lower total VFA concentration, and higher acetate-to-propionate ratio than AHR. CSR significantly enhanced the degradation of neutral detergent fiber and acid detergent fiber in both incubated forages (AH and CS). Although CSR did not improve the degradation of dry matter (DM) or crude protein (CP) on AH, it improved the degradation of DM and CP on CS. Both CS and AH incubated under CSR were found to have a greater abundance of fibrolytic bacteria (e.g., Fibrobacter and Butyrivibrio 2) compared to the same forage incubated under AHR, especially during the initial stages of incubation. However, CS and AH incubated under AHR were colonized by bacteria specialized in breaking down soluble carbohydrates (e.g., Prevotella and Succinivibrio). Compared with AHR, CSR enhanced the degradation rates of both incubated forages (CS and AH). These findings underscore the role of the rumen microenvironment in affecting the composition of adherent microbial communities and enhancing the breakdown of forages. Therefore, optimizing the rumen microenvironment to promote the attachment of fibrolytic bacteria during the early fermentation stages while minimizing hydrogen accumulation to stabilize the pH could lead to improved forage fermentation and animal performance.